2022
DOI: 10.3389/fcell.2022.839109
|View full text |Cite
|
Sign up to set email alerts
|

Elevated H3K4me3 Through MLL2-WDR82 upon Hyperglycemia Causes Jagged Ligand Dependent Notch Activation to Interplay with Differentiation State of Endothelial Cells

Abstract: Endothelial-to-mesenchymal transition (EndMT) is a hallmark of diabetes-associated vascular complications. Epigenetic mechanisms emerged as one of the key pathways to regulate diabetes-associated complications. In the current study, we aimed to determine how abrupt changes in histone 3 lysine 4 tri-methylation (H3K4me3) upon hyperglycemia exposure reprograms endothelial cells to undergo EndMT. Through in vitro studies, we first establish that intermittent high-glucose exposure to EC most potently induced parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…And signal transducer and activator of transcription 5A (STAT5A) has been reported to modulate latrophilin and seven transmembrane domain containing 1 (ELTD1) in order to regulate EndMT via a not well-characterized mechanism (113,114). Lastly, on the chromatin level, methylation of histone 4 lysine 20 (H4K20me1) by lysine methyltransferase 5A has been found to inhibit EndMT, while trimethylation of histone 3 lysine 4 (H3K4me3) by Set1 has been found to induce EndMT (115)(116)(117).…”
Section: Diabetic Nephropathy and Endothelialto-mesenchymal Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…And signal transducer and activator of transcription 5A (STAT5A) has been reported to modulate latrophilin and seven transmembrane domain containing 1 (ELTD1) in order to regulate EndMT via a not well-characterized mechanism (113,114). Lastly, on the chromatin level, methylation of histone 4 lysine 20 (H4K20me1) by lysine methyltransferase 5A has been found to inhibit EndMT, while trimethylation of histone 3 lysine 4 (H3K4me3) by Set1 has been found to induce EndMT (115)(116)(117).…”
Section: Diabetic Nephropathy and Endothelialto-mesenchymal Transitionmentioning
confidence: 99%
“…ECs isolated from human plaque show upregulated H3k27me3 when compared to ECs in regions without plaque (169). High levels of the histone modification H2K4me3 (histone 3 lysine 4 trimethylation) has been detected in the ECs of rat aortas exposed to hyperglycemia, which resulted in enriched expression of Notch and development of a mesenchymal-like phenotype (117). EZH2 has been found to be upregulated in atherosclerosis as well as in ECs treated with high glucose (168-170).…”
Section: Endothelial-to-mesenchymal Transition and Macrovascular Comp...mentioning
confidence: 99%
“…Numerous studies have already revealed that histone methylation plays an essential role in DKD progression, especially H3K4me3 with its conserved distribution on gene promoters [ 44 , 45 ]. High levels of H3K4me3 were associated with inflammatory and oxidative stress, progressive proteinuria through podocyte injury, and fibrosis [ 44 46 ], thus participating in DKD progression. Hypoxia was shown to rapidly increase histone methylation and chromatin reprogramming at various sites [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For immunofluorescence studies, kidney slices were deparaffinized and submitted to antigenic retrieval with EDTA buffer (1mM EDTA, 0.05% Tween 20, pH 8) ( 19 , 20 ). After blocking (Protein Block, DAKO Agilent Technologies Inc., Saint Clair, CA USA) for 1 hour, sections were incubated overnight at 4° C using the following primary antibodies: mouse anti-collagen IV (1:400, Abcam, Cambridge, UK); rabbit anti-TET1 (1:150, Genetex, Radnor, PA USA); rabbit anti-TET3 (1:100, Novus Biotechnology, Centennial, CO USA); and rabbit anti-Wilms’ tumor suppressor 1 (WT1) (1:200, Novus Biotechnology).…”
Section: Methodsmentioning
confidence: 99%